Time-varying pricing of risk in sovereign bond futures returns - Barbora Malinska (Charles University in Prague, Institute of Economic Studies (IES), 2020)
We examine time-varying explanatory power of realized moments on subsequent bond futures excess returns using more than 12 years of high-frequency data from U.S. and German sovereign bond markets. We detect realized volatility and realized kurtosis to carry valuable information for next-day open-close excess returns on the U.S. market which is not priced in traditional bond return predictors such as term or default spreads. Most importantly, we reveal the bond excess return predictability to be significantly dynamic and to increase during crisis period. Whereas the realized volatlity reveals to have negative effect on next-day excess returns, effect of realized kurtosis is switching from positive effect in the time of 2007-2009 financial crisis to negative values after 2014.
Keywords: C32; C55; G12; 330; Realized moments; bond pricing; risk-return trade-off; high-frequency data; time-varying coeffcients